Controlled Oxygenated Rewarming Compensates for Cold Storage–induced Dysfunction in Kidney Grafts. Issue 5 (23rd June 2021) - von Horn, Charlotte; Zlatev, Hristo; Kaths, Moritz; Paul, Andreas; Minor, Thomas
Abstract : Background: Normothermic machine perfusion (NMP) provides a promising strategy for preservation and conditioning of marginal organ grafts. However, at present, high logistic effort limits normothermic renal perfusion to a short, postponed machine perfusion at site of the recipient transplant center. Thus, organ preservation during transportation still takes place under hypothermic conditions, leading to significantly reduced efficacy of NMP. Recently, it was shown that gentle and controlled warming up of cold stored kidneys compensates for hypothermic induced damage in comparison to end ischemic NMP. This study aims to compare controlled oxygenated rewarming (COR) with continuous upfront normothermic perfusion in a porcine model of transplantation. Methods: Following exposure to 30 min of warm ischemia, kidneys (n = 6/group) were removed and either cold stored for 8 h (cold storage [CS]), cold stored for 6 h with subsequent controlled rewarming up to 35 °C for 2 h (COR), or directly subjected to 8 h of continuous NMP. Kidney function was evaluated using a preclinical autotransplant model with follow-up for 7 d. Results: NMP and COR both improved renal function in comparison to CS and displayed similar serum creatinine and urea levels during follow-up. COR resulted in less tenascin C expression in the tissue compared with CS, indicating reduced proinflammatory upregulation in the graft by gentle rewarming. Conclusions: COR seems to be a potential alternative in clinical application of NMP, thereby providing logistic ease and usability.